2003
DOI: 10.1046/j.1538-7836.2003.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to treatment of bleeding episodes in young hemophilia patients: a single bolus megadose of recombinant activated factor VII (NovoSeven®)

Abstract: Summary. Recombinant activated factor VII (rFVIIa, NovoSeven 1 ) represents an effective treatment for hemophilia patients with inhibitors, but no consensus as to the best dosing regimen exists. We assessed the efficacy and safety of a rFVIIa 'megadose' (300 mg kg À1 bolus) as treatment for bleeds in three young inhibitor patients. Of 114 bleeds, 95 responded to a single dose. Pain relief was faster and therapy duration significantly shorter than with continuous infusion (CI) regimens or standard boluses (90 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
119
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 25 publications
5
119
0
2
Order By: Relevance
“…Recent developments suggest that doses higher than those recommended may be more efficacious in patients with hemophilia and may require dosing at less frequent intervals. 32,33 Constant infusion regimens for the use of rfVIIa have also been described and have been used successfully. 34 With this regimen it may be possible to use less rfVIIa when compared with treatment regimens using bolus doses.…”
Section: Dosage Of Recombinant Factor Viiamentioning
confidence: 99%
See 2 more Smart Citations
“…Recent developments suggest that doses higher than those recommended may be more efficacious in patients with hemophilia and may require dosing at less frequent intervals. 32,33 Constant infusion regimens for the use of rfVIIa have also been described and have been used successfully. 34 With this regimen it may be possible to use less rfVIIa when compared with treatment regimens using bolus doses.…”
Section: Dosage Of Recombinant Factor Viiamentioning
confidence: 99%
“…33 Of 114 bleeding episodes, 95 responded to a single 300-g dose of rfVIIa without side effects. The remaining patients responded to subsequent similar doses of rfVIIa.…”
Section: Dosage Of Recombinant Factor Viiamentioning
confidence: 99%
See 1 more Smart Citation
“…Children especially seem to require higher doses per injection than adults for an optimal effect. 7,8 In most cases an optimal dose seems to be achievable if doses are individualized. 8 -10 However, in some special situations the rapid formation of a strong fibrin plug may be necessary to restore hemostasis.…”
mentioning
confidence: 99%
“…However, its short plasma half-life requires a short interval for follow-up dosing and limits its application in prophylaxis. In addition, clinical studies have suggested that higher initial doses may result in a more rapid onset of hemostasis, 39,40 and the time from initiation of bleeding to initiation of treatment may have a significant impact on efficacy. 41 Accordingly, several bioengineering strategies have been implemented in an attempt to improve rFVIIa functionality.…”
Section: Bioengineered Activated Factor VIImentioning
confidence: 99%